EFEKTIFITAS PEMBELAJARAN FIQIH IBADAH DALAM PRAKTIK IBADAH MADRASAH TSANAWIYAH (MTs) KEBUNREJO GENTENG - Ahmad Hasyim Fauzan (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2019)
The effectiveness of the fiqh of worship in the practice of worship in Madrasah Tsanawiyah Kebunrejo Genteng. The Program aims to provide knowledge of learners about the ordinance of ablution and prayer, so that they can perform the worship properly and in accordance with Islamic law, and can be practiced And can be habituation in the daily life of learners. The results of this dedication program are expected to increase the contribution of discourse and science of science in the field of Islamic religious education, adding knowledge of research and devotion about the fiqh of worship and effectiveness of learning. The methods used in delivering material vary among others: CCA, lectures, fairy tales, games. The supporting factor is the delivery of materials that use various methods, parents who always supervise the child, ustadz whose knowledge of the material is already capable. While the avoidance factor is: the classes are less conditioned and not all students can capture the material delivered with the same method.